2010
DOI: 10.1111/j.1365-3148.2010.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of platelets for bacterial contamination at the Welsh Blood Service

Abstract: The bacterial screening system has removed a significant number, but not all bacterially contaminated platelet components from the supply. The sample volume is an important factor in sensitivity due to the low number of bacteria in a platelet component pack on day 1. An effective notification and recall system is a critical part of the bacterial screening system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(117 citation statements)
references
References 23 publications
6
110
1
Order By: Relevance
“…Firstly, the use of an anaerobic culture bottle extends the bacterial spectrum that can be identified as a contamination. This benefit has been confirmed by several reports [11, 18, 39, 40]. For instance, a study from NHS Blood and Transplant showed that 66% of all confirmed positive results were only detected in anaerobic culture bottles, whereas 8% were positive in an aerobic and 26% in both bottle types [17].…”
Section: Anaerobic Screening – Is It Worth the Effort?supporting
confidence: 66%
“…Firstly, the use of an anaerobic culture bottle extends the bacterial spectrum that can be identified as a contamination. This benefit has been confirmed by several reports [11, 18, 39, 40]. For instance, a study from NHS Blood and Transplant showed that 66% of all confirmed positive results were only detected in anaerobic culture bottles, whereas 8% were positive in an aerobic and 26% in both bottle types [17].…”
Section: Anaerobic Screening – Is It Worth the Effort?supporting
confidence: 66%
“…If the instrument detects bacterial growth in the bottle it is flagged and the corresponding platelet unit is discarded. While this process is reasonably successful at detecting fast growing organisms, many of the slow growing species do not grow to a high enough titer to be detected, thus creating the potential for false-negative units to be released for transfusion 7,12,14,16,22 . Unlike culture based detection systems, rapid point of care testing is typically performed later in the platelet storage period when the bacterial load has increased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that the bacterial load at the time of contamination is low, <100 colony forming units (CFU)/product 2,16 , however the nutrient rich environment and room temperature storage allows contaminating bacteria to proliferate to dangerously high titers prior to transfusion. Currently, the only approved methods available to prevent bacterially contaminated products from reaching a platelet recipient is through the use of culture based systems and rapid point of care testing.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of routine bacterial detection methods to screen platelets for bacterial contamination can further reduce but not completely eliminate the risk of PC-transmitted bacterial infection [34]. Bacterial detection assays only detect less than 40% of contaminated products [35,36]. Therefore, comprehensive protection from bacterial infections including fatal sepsis transmitted by contaminated PCs remains the major reason for implementation of PI.…”
Section: Discussionmentioning
confidence: 99%